2010
DOI: 10.1143/apex.3.054001
|View full text |Cite
|
Sign up to set email alerts
|

A Cooper-Pair Light-Emitting Diode: Temperature Dependence of Both Quantum Efficiency and Radiative Recombination Lifetime

Abstract: A light-emitting diode (LED) in the optical-fiber communication band showed special features after replacing the n-type electrode with niobium (Nb) superconducting metal. Nb electrodes prepared on an InGaAs-based semiconductor surface formed a superconductor/semiconductor/superconductor junction, and the current-voltage characteristics exhibited both DC and AC Josephson junction properties. This was a result of the injection of electron Cooper-pairs into the n-InGaAs active layer of an LED. The drastic enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 10 publications
5
30
1
Order By: Relevance
“…This description can be regarded as a new-type JoFET, and we emphasize the difference from the conventional JoFET 9 where the carrier density in semiconductor (normal conductor) is modulated by the gate voltage. The estimated value of superconducting pair density n p (3.4 × 10 15 cm −3 ) is comparable to those estimated in other superconductor-based LEDs 5 . When the steady current injection takes place in the current-injected region of V G ≥ 0.78 V, both of I c and R n decrease.…”
Section: Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…This description can be regarded as a new-type JoFET, and we emphasize the difference from the conventional JoFET 9 where the carrier density in semiconductor (normal conductor) is modulated by the gate voltage. The estimated value of superconducting pair density n p (3.4 × 10 15 cm −3 ) is comparable to those estimated in other superconductor-based LEDs 5 . When the steady current injection takes place in the current-injected region of V G ≥ 0.78 V, both of I c and R n decrease.…”
Section: Methodssupporting
confidence: 83%
“…In spite of the large mismatch in the energy scale, it is also predicted that the coherence of superconducting pair system can be transferred to photon systems [1][2][3] . The radiative recombination process in superconductor-based LED has been investigated by optical measurements, which revealed the enhanced oscillator strength 4 , high quantum efficiency and radiative recombination time rapidly decreasing with temperature [5][6][7] . In transport measurements, on the other hand, the diffusion of superconducting pairs into the active layer was demonstrated by DC and AC Josephson effect, and the monitoring sensitivity of the radiative recombination process was found to be several orders higher than that in optical measurements although the cause of this ultrahigh sensitivity has not been elucidated 5,6,8 .…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that the observed luminescence enhancement is well explained with the theory. 13 We also observed sharp reduction of the LED luminescence decay time constant with another SC-LED below T C , and also demonstrated a good agreement with our theory. 14,15 With these results, we evidenced the active role of Cooper pairs in radiative recombination in SC-LEDs.…”
Section: Introductionsupporting
confidence: 88%
“…The luminescence intensity shows sharp increase below T C of 9.07 K. This well reproduces our previous observation of luminescence enhancement in SC-LEDs. 11,13 Above T C the decay time constant remains the same, but below T C it shows clear decrease with temperature. This also well reproduces our previous observation of decrease of the electroluminescence decay time constant in SC-LEDs.…”
Section: Time-resolved Luminescence Measurementsmentioning
confidence: 90%
See 1 more Smart Citation